2016
DOI: 10.1016/j.jcmgh.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Glycans Related to the CA19-9 Antigen Are Increased in Distinct Subsets of Pancreatic Cancers and Improve Diagnostic Accuracy Over CA19-9

Abstract: Background and Aims The CA19-9 antigen is the current best biomarker for pancreatic cancer, but it is not elevated in about 25% of pancreatic cancer patients at a cutoff that gives a 25% false-positive rate. We hypothesized that antigens related to the CA19-9 antigen, which is a glycan called sialyl-Lewis A (sLeA), are elevated in distinct subsets of pancreatic cancers. Methods We profiled the levels of multiple glycans and mucin glycoforms in plasma from 200 subjects with either pancreatic cancer or benign … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 38 publications
0
34
0
Order By: Relevance
“…In fact, a relevant issue to be addressed concerns the potential expression of sLe x in conjunction or alternative to CA19.9. Recently, it was proposed that CA19.9-negative cancer patients may be monitored through circulating sLe x [134], and the expression of sLe x in distinct glycans appears to be independent of that of sLe a , potentially improving the diagnostic accuracy over CA19.9 [135]. The expression of sLe x on plasma protein seems to be actually associated with gastrointestinal cancers, as above reported [96].…”
Section: Role In Diagnosismentioning
confidence: 91%
“…In fact, a relevant issue to be addressed concerns the potential expression of sLe x in conjunction or alternative to CA19.9. Recently, it was proposed that CA19.9-negative cancer patients may be monitored through circulating sLe x [134], and the expression of sLe x in distinct glycans appears to be independent of that of sLe a , potentially improving the diagnostic accuracy over CA19.9 [135]. The expression of sLe x on plasma protein seems to be actually associated with gastrointestinal cancers, as above reported [96].…”
Section: Role In Diagnosismentioning
confidence: 91%
“…Sialyl-Le x/a , which are expressed either protein- or lipid-bound on the cell surface, have their expression increased in different types of cancer, including gastric, colorectal, oral squamous cell, and pancreatic cancer [141-144]. During the metastasis process, they act as carbohydrate ligands for E-selectin-mediated cancer cell adhesion [145].…”
Section: Hypoxia Changes Membrane Glycoconjugates In Tumor Cellsmentioning
confidence: 99%
“…The sialy-Lewis X glycan showed elevations in 30%-50% of the patients with low CA19-9 but also showed elevations in about 10% of patients with benign pancreatic diseases. Another glycan, referred to as sTRA, was elevated in up to half of the patients with low CA19-9, with very low false-positive rates (7). In subsequent research, we found that the cells producing sTRA are different in location, morphologies, and molecular characteristics than the cells producing CA19-9 (8).…”
Section: Introductionmentioning
confidence: 74%